POLA PENGUASAAN DAN KEPEMILIKAN TANAH PADA MASYARAKAT SUKU HATAM DI KECAMATAN WARMARE KABUPATEN MANOKWARI TAHUN 1950 - 1972 - MANDACAN, AGUS ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: The practice of land tenure on Hatam tribal society has undergone a shift due to the influence of immigrants. This shift more pronounced upward in 1962 as the development is increasingly improved. Number of Hatam people is growing, but the communal land is increasingly limited. Values magical religious (sacred relationship between man and land) to fade. Development on lands Hatam tribal has not been able to improve their welfare. The structure of vertical relationships in the Hatam tribe community is also often associated with land issues. Soil indicates a person's status in Hatam tribe society. Objectives: To analyze the factors that cause a shift in the traditions of land ownership tenure, studying the effects caused by the shift in the tradition of land tenure in Hatam tribal communities in the Sub Warmare Manokwari District. Methods: This study is a historical research. The data collected was tested by internal and external criticism. Internal criticism to test credibility (feasibility) of data, while the external criticism to examine the authenticity (validity) of data. This study also uses a sociological approach to explaining aspects of land tenure in Hatam tribal people, and the power of chiefs and the colonial government that led to the emergence of a shift in Hatam tribal people land tenure. Results: Results showed that the tradition of land ownership tenure at Hatam tribal society is determined by the system of inheritance, grants, land transfer and exchange. Factor contributing to the shift in Hatam tribe land ownership tenure traditions include marriage, the credibility of the chieftain, motivation to be timor fabric ownership, economic and educational needs, and a touch of development. The influence caused by the shift of Hatam tribe land ownership tenure traditions includes positive and negative influences. Conclusion: Shift in the tradition of Hatam tribe land tenure has a positive effect on access of transport, information access, social interaction, access to economic needs, employment, health, education, and welfare of Hatam tribal people. Negative influences include economic and educational needs are met is difficult, emerging social jealousy, sacred relationship between land and hatam communities disrupted, horizontal conflicts arise, the process of acceleration of development in Hatam tribal obstructed, the higher the social disease, the level of public trust to government and their participation in the development of increasingly reduced, and the emergence of two important issues due to the implementation of development are met, namely the failure of the resettlement project and prolonged disputes between the clan.